Hypotension does not always make computed tomography scans unfeasible in the management of blunt abdominal trauma patients. Issue 1 (January 2015) - Fu, Chih-Yuan; Yang, Shang-Ju; Liao, Chien-Hung; Lin, Being-Chuan; Kang, Shih-Ching; Wang, Shang-Yu; Yuan, Kuo-Ching; Ouyang, Chun-Hsiang; Hsu, Yu-Pao
Abstract Introduction Computed tomography (CT) scans have been used worldwide to evaluate patients with blunt abdominal trauma (BAT). However, CT scans have traditionally been considered to be a part of a secondary survey that can only be performed after the patient's haemodynamics have stabilised. In this study, we attempted to evaluate the role of the CT scan in managing BAT patients with hypotension. Material and methods Patients who fulfilled the criteria for a major torso injury in our institution were treated according to the Advanced Trauma Life Support guidelines. The selection of diagnostic modalities for patients with stable and unstable haemodynamics was discussed. Furthermore, patients with hypotension after resuscitation who were administered haemostasis procedures were the focus of our analysis. We also delineated the influence of CT scans on the time interval between arrival and definitive treatment for these patients. Results During the study period, 909 patients were enrolled in this study. Ninety-one patients (10.0%, 91/909) had a systolic blood pressure (SBP) <90 mmHg after resuscitation. Fifty-eight of the patients (63.7%) received CT scans before they received definitive treatment. There was no significant difference in the CT scan application rate between the patients with and without hypotension after resuscitation (63.7% vs. 68.8%, p = 0.382). Among the 79 patients with hypotension after resuscitation who underwent a haemostasis procedure (surgery or angioembolisation), there was no significant difference in the time between arrival and definitive haemostasis between the patients who received CT scans and those who did not (surgery: 57.8 (standard deviation (SD) 6.4) vs. 61.6 (SD 14.5) min, p = 0.218; angioembolisation: [147.0 (SD 33.4) vs. 139.3 (SD 16.7) min, p = 0.093). Conclusion The traditional priority of diagnostic modalities used to manage BAT patients should be reconsidered because of advancements in facilities and understanding of BAT. With shorter scanning times and transportation distances, hypotension does not always make performing a CT scan unfeasible.